2015
DOI: 10.1021/acs.jpcc.5b03289
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Al Distribution in the Framework of ZSM-5 Zeolite and Its Evaluation by Solid-State NMR Technique and Catalytic Properties

Abstract: 13The effects of the organic structure-directing agents (OSDAs) and Na cations for the synthesis of 14 ZSM-5 on the location of Al atom in the framework as well as the acidic and catalytic properties were 15 investigated. To achieve these purposes, ZSM-5 zeolites were synthesized by using four kinds of 16 organic structure-directing agents (OSDAs) including tetrapropylammonium hydroxide cations, 17 dipropylamine, cyclohexylamine and hexamethyleneimine with or without Na cations. In-situ FT-IR 18 spectroscopy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
199
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(215 citation statements)
references
References 56 publications
13
199
0
3
Order By: Relevance
“…For zeolites, one prototypical case is 29 Si, sensitive to bond distances, angles, and next‐nearest‐neighbor environment: its usefulness in probing the Si/Al ordering in zeolites has been long recognized . Besides 29 Si, also 27 Al plays a key role in topical issues, like characterization of zeolitic acid sites, or nucleation and growth processes, while 33 P is especially relevant for aluminophosphates. Many other nuclei ( 1 H, 2 H, 13 C, 15 N, etc.)…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…For zeolites, one prototypical case is 29 Si, sensitive to bond distances, angles, and next‐nearest‐neighbor environment: its usefulness in probing the Si/Al ordering in zeolites has been long recognized . Besides 29 Si, also 27 Al plays a key role in topical issues, like characterization of zeolitic acid sites, or nucleation and growth processes, while 33 P is especially relevant for aluminophosphates. Many other nuclei ( 1 H, 2 H, 13 C, 15 N, etc.)…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…As depicted in the MD snapshots (Figure c), nevertheless, the structural matching did not allow for the free movement and rotation of OSDAs, providing the chance of OSDAs to control the Al locations. Another structural reason for selecting IFR zeolite is that its crystal structure has four distinct crystallographic T sites (Figure d), making quantitative determination of Al occupancy possible by the 27 Al MQMAS NMR technique as this technique is not able to distinguish Al sites in zeolite structures containing too many T sites such as *BEA and MFI zeolites …”
Section: Figurementioning
confidence: 99%
“…As a result, the interactions between OSDAs and anionic charges near Al sites are inconstant, leading to broad distributions of Al over T sites. Yet, the Al locations can be controlled in zeolite framework positions between different cavities (e.g., large vs. small cages) but not crystallographic site specific ,. In the latter situation, the T site‐specific Al can be achieved due to the low mobility of OSDAs, providing the specificity of the structure‐directing ability …”
Section: Figurementioning
confidence: 99%
“…Thus, knowledge of the effect of Na + ions on the location of Al atoms in the zeolite channel system is of crucial importance. Recently Tatsumi and co‐workers reported a comparison regarding the constraint indices for cracking of n ‐hexane and 3‐methyl pentane over ZSM‐5 zeolites synthesized either by employing exclusively TPA + or TPA + and Na + as SDAs . They suggested that the application of only TPA + led to Al atoms located at channel intersections.…”
Section: Figurementioning
confidence: 99%